The Influence of System Quality, Information and Services of the Merdeka Mengajar Platform on User Satisfaction in Elementary School - Adnin Purnama Sari; Syaiful Bakhri (FITK UIN Walisongo Semarang, 2024)
This study aims to determine the effect of system quality, information and services from the Merdeka Mengajar Platform on user satisfaction at SDN Tambakaji 04 and SDN Ngaliyan 01 Semarang. This study used quantitative research methods with a population of 50 teachers. Making a questionnaire prepared usingscale likertscale 1-5. The results of the analysis of hypothesis testing (t test): 1) system quality obtained a sig value of 0.842 > 0.05, which means that the quality of the independent Merdeka Mengajar Platform (PMM) system has no significant effect on user satisfaction at SDN Ngaliyan 01 and SDN Tambakaji 04 Semarang, 2) results of the t-test for the quality of information obtained sig 000 <0.05, meaning that the quality of independent Merdeka Merdeka platform (PMM) information has a significant effect on user satisfaction at SDN Ngaliyan 01 and SDN Tambakaji 04 Semarang, and 3) results of the t-test for quality service obtained a value of 000 <0.05, meaning that service quality has a significant effect on user satisfaction at SDN Ngaliyan 01 and SDN Tambakaji 04 Semarang.